Effect of Heating Temperature and Die Insert Draft Angle on the Flowability of Hot Forged SCM435 Steel - Sofyan, Nofrijon; Heruwiyono, Maulana; Yuwono, Akhmad Herman; Dhaneswara, Donanta (National Research and Innovation Agency (BRIN), 2022)
The problem of flowability in a closed forging process for heavy equipment industry is still widely found and this may affect the quality of the resulting product. To obtain the solution for this problem, in this work, the effect of heating temperature and die insert draft angle on the characteristic of hot forged SCM435 steel used for undercarriage track roller has been examined. The workpieces were heated at temperature variations of 1150 °C, 1200 °C, 1250 °C and were hot forged at die insert draft angles of 3°, 5°, and 7° to form undercarriage track roller products. The mechanical properties of the products were characterized through hardness and dimension examination, whereas the microstructure was characterized using an optical microscope. The results showed that increasing the heating temperature and die insert draft angle resulted in good flowability. The best result was obtained from the heating temperature of 1250 °C at the die insert draft angle of 7°, with diameter and height of 191.2 mm and 53.6 mm, respectively. This characteristic of the obtained hot-forged product agreed with that of the specified forging design for the undercarriage track roller